Implications of Gut Microbiota in Neurodegenerative Diseases - Zhang, Haoming; Chen, Yijia; Wang, Zifan; Xie, Gaijie; Liu, Mingming; Yuan, Boyu; Chai, Hongxia; Wang, Wei; Cheng, Ping (Frontiers in Immunology, 2022)
The morbidity associated with neurodegenerative diseases (NDs) is increasing, posing a threat to the mental and physical quality of life of humans. The crucial effect of microbiota on brain physiological processes is mediated through a bidirectional interaction, termed as the gut–brain axis (GBA), which is being investigated in studies. Many clinical and laboratory trials have indicated the importance of microbiota in the development of NDs via various microbial molecules that transmit from the gut to the brain across the GBA or nervous system. In this review, we summarize the implications of gut microbiota in ND, which will be beneficial for understanding the etiology and progression of NDs that may in turn help in developing ND interventions and clinical treatments for these diseases.